ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KEMBALI DI KAYU KAYU RESTAURANT ALAM SUTERA - Radella Paramitta; Sofiani Sofiani (Jurnal Ilmiah Global Education, 2023)
Kayu Kayu Restaurant Alam Sutera has a poor lighting system, a good and relaxed atmosphere with a floral aroma that has aromatherapy. Kayu Kayu Restaurant Alam Sutera has a homey atmosphere. The purpose of this research is to determine the store atmosphere of Kayu Kayu Restaurant Alam Sutera. The method used is quantitative, data collection techniques are questionnaires, observation, and documentation. The number of samples is 399 respondents. The results of the study show that the T test is that each dimension that is owned by the store atmosphere variable (X) has a partial influence on the repurchase decision (Y). The results of the F test indicate that the store atmosphere variable has a simultaneous influence on the repurchase decision variable. Test results for the Coefficient of Determination (R2) of 97.5% because the Store Exterior (X1) is a nameplate that is easy to recognize, the main door is ready to go in and out, attractive design, adequate parking facilities, guaranteed vehicle safety, General Interior (X2) is bright lighting, bright wall colors bright, comfortable music, soothing aroma and cool temperature, Store Layout (X3), which is a complete and clean facility, neat arrangement of items, sufficient table & chair arrangements for passing, Display (X4), namely signs and instructions clear price tag, and a nice Store Atmosphere (X5).